Evaluation of polyurethane and polyurethane /polyvinyl chloride blend coatings on steel as corrosion protection using EIS technique - Alsamuraee, Abdul-Karim M. A. (Iraqi Journal of Physics, 2010)
This paper was aimed to evaluate the polyurethane (PU) and polyurethane/polyvinyl chloride (90 wt. % / 10 wt. %) as organic coating of carbon steel substrate against marine environment (3.5 wt.% NaCl aqueous solution) as a severe corrosion environment . The electrochemical impedance spectroscopy (EIS) and fitting impedance data by ZsimpWin 3.22 software were used to estimate the physical barrier of the samples for different exposure times. Different equivalent electrical circuits were proposed for the physical barrier at different immersion times to get appropriate fitting .Both PU and PU/PVC coatings showed excellent corrosion protection ability for steel .The PU/PVC coating showed better protection and stability than PU coating against aggressive salt solution. The relation between dielectric properties (impedance spectrum) of coating film with their behavior as physical barrier protection gave useful information about electrochemical process and predicts the barrier protective behavior in natural environment.